Self-regulation as Correlates to Students’ Voices and Achievement in TOEFL Score - Monika Dini Kurniasari (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Students’ engagement and persistence in test preparation require their use of self-regulated learning strategies to negate distraction and facilitate good preparation. This research aimed to investigate students’ self-regulation strategies when taking a TOEFL preparation course, by measuring their attitudes towards the course and analyzing the correlation between their pre-test and progress test scores. The data collected comprised self-reported answers from a Motivated Strategies for Learning Questionnaire and the scores of a pre-test and progress test taken by the students during the course. The students were cognizant that hard work affected learning performance, valuing in particular overcoming difficult tasks or continuing to learn even when performance lagged. A strong positive correlation was also found between pre-test and progress test scores (r = 0.8422), indicating high academic performance in the students. These findings emphasize the importance of developing students’ methods of learning and practice. Students should be empowered to become regulated-learners, and should be made more aware of different self-regulated learning strategies to better evaluate, regulate, and improve their own performance.